Effect of voluntary disclosure level, ownership structure and proprietary cost on the return-earnings relation : Singapore evidence. - Luo, Shuqing. (2008)
This study explains how voluntary disclosure activity affects the relationship between current annual return, contemporaneous annual earnings and future earnings, and whether or not management ownership and proprietary cost moderates this relationship.